Non-Isothermal flow of Third Grade Fluid with Thermal Radiation through a Porous Medium - A. B. Sikiru; S. A. Idowu; O. W. Lawal (Journal of Applied Sciences and Environmental Management)
A mathematical model is analyzed to study the effect of various physical parameters related to non-isothermal flow of third grade fluid in the presence of thermal radiation through a porous medium. Hence, the objective of this paper is to investigate the combined impacts of magnetic field, viscous dissipation, thermal radiation, varying thermal conductivity and viscosity on non-isothermal flow of a third grade fluid with thermal radiation through a porous medium. The Galerkin weighted residual method was used to solve the resulting non-linear ordinary differential equations numerically. The graphic representation and discussion of the effect of various significant parameters on the flow system are presented. The investigation of this problem leads to the conclusion that the thermal radiation parameter, the variable thermal conductivity and viscosity parameters have a significant impact on the mass flow and the energy transfer phenomena in the system.